Academic stress level in nursing students during the COVID-19 pandemic - Asenjo-Alarcón, José A. (2021)
Introduction. The COVID-19 pandemic has had a negative impact on the emotional health of the population, with different and inappropriate responses depending on the affected group. The research aimed to estimate the level of academic stress in nursing students from the National Autonomous University of Chota, Peru, during the COVID-19 pandemic. Methods. Observational, cross-sectional study, carried out in 122 nursing students from I to X cycle, they responded to the SISCO SV Academic Stress Inventory. Results. The level of academic stress in the stressors dimension was severe in women (64.4%) and men (77.2%), in the symptom dimension it was severe in women (42.5%) and mild in men (48.6 %) and in the dimension of coping strategies, it was severe in women (62.1%) and men (60.0%). The most frequent stressors were: task and work overload (66.4%), limited time for work (64.8%), level of demand from teachers (58.2%), exams or practices (58.2%) , teacher evaluation forms (54.1%), type of jobs requested (54.1%) and highly theoretical teachers (53.3%); the most frequent symptom was headaches (45.1%); the most used coping strategies were: listening to music or watching television (54.9%), surfing the internet (53.3%), assertive ability (51.6%), concentrating on solving the situation (49.2%) and entrust themselves to God (48.4%). The level of global academic stress was severe in women (51.7%) and men (48.6%). Conclusion. Nursing students of both sexes presented a level of severe academic stress in the dimensions and in the global assessment.